Unpreparedness during Disastrous Attacks: The View of South Africa Category B Municipalities - Nonzwakazi Beauty Makiwane; Chuma Sikwati (International Journal of Law, Social Science, and Humanities, 2026)
Disasters have become an unavoidable part of life worldwide. In South Africa, the frequency and severity of both natural and man-made disasters highlight the urgent need for effective disaster preparedness at the municipal level. Although significant progress has been made in disaster risk management policies, Category B municipalities in South Africa still face challenges associated with preparedness. The article examines the main factors contributing to disastrous incidents in South African Category B municipalities and early warning systems that evoke effective disaster readiness. Its purpose is to disclose the consequential influential perceptions of disaster management officials directly involved in disaster incidents in five Category B local municipalities (King Sabata Dalindyebo, Mhlontlo, Nyandeni, Port St. Johns, and Ingquza) incorporated in O.R. Tambo district. A qualitative approach was used, based on an interpretive framework. Twenty disaster management officials, considered key informants, completed self-administered, face-to-face, open-ended questionnaires, with follow-up interviews to clarify responses. The data were analyzed through content analysis to identify and interpret themes. The findings emphasize the need for comprehensive, long-term disaster preparedness strategies and resilience plans tailored to the specific challenges faced by Category B municipalities in South Africa. Fostering democratic principles, ensuring local responsiveness, and maintaining global competitiveness through partnerships and collaboration must be strengthened and maintained by South Africa’s Category B municipalities to achieve the Millennium Development Goals, the Sustainable Development Goals, the National Development Plan, and the African Union's Agenda 2063 is demonstrated by their notable readiness during catastrophic events. Keywords: Unprepared disastrous attacks, Category B municipalities, disaster management officials